2009
DOI: 10.1038/oby.2009.5
|View full text |Cite
|
Sign up to set email alerts
|

Youth BMI Trajectories: Evidence From the NLSY97

Abstract: We examined heterogeneity in BMI trajectory classes among youth and variables that may be associated with trajectory class membership. We used data from seven rounds (1997–2003) of the 1997 National Longitudinal Survey of Youth (NLSY97), a nationally representative, longitudinal survey of people born between 1980 and 1984 who were living in the United States in 1997. The analyses were based on an accelerated longitudinal design. General growth mixture modeling implemented in Mplus (version 4.1) was used to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
102
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 19 publications
16
102
2
1
Order By: Relevance
“…The difference in findings may be due to the different age groups studied as well as the different ways that smoking was measured. In this study, smoking was measured in years and considered as a TVC, whereas smoking status was measured once and considered as a time-constant variable in the study by Nonnemaker et al [22]. In another BMI trajectory study, the researchers utilized CGM and found that smoking was associated with a lower BMI at baseline and a slower rate of change over time [59].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The difference in findings may be due to the different age groups studied as well as the different ways that smoking was measured. In this study, smoking was measured in years and considered as a TVC, whereas smoking status was measured once and considered as a time-constant variable in the study by Nonnemaker et al [22]. In another BMI trajectory study, the researchers utilized CGM and found that smoking was associated with a lower BMI at baseline and a slower rate of change over time [59].…”
Section: Discussionmentioning
confidence: 99%
“…Within each trajectory group, the values of average posterior probability of group membership were ascertained [19]. The trajectory analysis was conducted separately for women and men because of the compelling evidence of gender differences in obesity [5,22,25,28,42,54].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these reductions are modest, they are noteworthy given the typical trajectory of weight gain from adolescence into adulthood without intervention. 26 An additional potential benefit of this type of intervention is improved self-concept, which is typically diminished among overweight teenagers.…”
Section: Discussionmentioning
confidence: 99%